Misdiagnosis of primary angiosarcoma of the breast: A case report - Yinuo, Qi; Luo, Jing (Current problems in cancer. Case reports, 2025)
•Breast angiosarcomas are rare and aggressive tumors with generally poor prognosis and difficulties in diagnosis as most of them have non-specific imaging findings and eventually depend on microscopic examination together with immunohistochemical staining. So we present a case to provide radiological and pathological findings for reference and research.•As mentioned, the diagnosis of breast angiosarcomas can be difficult. We elaborated on the problems we encountered in our practice and learned from them how to better avoid misdiagnosis.•Due to the rarity of PAS, it is difficult to establish a well-tested treatment agent. We established a unique treatment plan for this patient based on her condition combined with the results of previous studies. This can be used for reference. Breast angiosarcoma is a rare and aggressive tumor with a generally poor prognosis. Given its lack of pathognomonic symptoms and non-specific imaging findings, diagnosis is challenging and mostly depends on pathological reports. Optimal management is still unclear and controversial. Herein reported is a case of post-menopausal primary breast angiosarcoma. A 65-year-old lady, presented with a large palpable mass in her left breast. Mammogram findings were non-specific, but Ultrasound and Magnetic Resonance Imaging (MRI) raised high suspicion of vascular origin. A core needle biopsy was taken through the mass, with the pathology report indicating breast adenosis. Then she received lumpectomy, but the microscopic examination and immunohistochemistry staining of excised tissue suggested well-differentiated angiosarcoma. Three months after her initial surgery, she underwent a further mastectomy. Taking the tumor size and histological grade into consideration, subsequent adjuvant therapy is not recommended, but the frequency of follow-up should be increased. She is still alive. Pathognomonic signs on radiological imaging, especially MRI, do help in characterizing these tumors and raising the suspicion of vascular endothelial origins of them. Ultrasound-guided biopsy is recommended to get an early diagnosis, but in some cases, due to the limited sample size, it can be mistaken for benign lesion or false negative results may be given too. This could delay the diagnosis and efficient treatment of this aggressive malignancy. We recommend that physicians pay more attention when encountering radiology-pathology incoherence and should consider the need to review the results again or obtain additional samples that have yielded more accurate pathology results.